Economic analysis of residential solar photovoltaic systems in China. (1st February 2021) - Qiu, Shoufeng; Wang, Ku; Lin, Boqiang; Lin, Ping
Abstract: Residential solar photovoltaic (PV) installations have boomed in China over recent years. However, knowledge about the economic performance of residential PV investments is still limited. Therefore, this study attempts to make a complete economic assessment of residential PV systems at the county-level. After a brief description of China's incentive policies, a model is constructed with economic measures of internal rate of return and payback period based on discounted cash flow. Then, a reference PV system of 5 kWp is investigated in 2181 geographical areas using scenario analysis and sensitivity analysis. There is breakeven for residential PV investments all over China even without incentives. The areas with good performance of residential PV investments are located mostly in Northern China (Shandong and Hebei), Southern China (Guangdong and Hainan), northeast China (Liaoning, Jilin, and Heilongjiang), and southwest China (Sichuan and Tibet). The boom of residential PV installations is likely to recede in 2021 as the population with acceptable profitability declines since the central and local subsidies expire. But some excellent residential PV suppliers have the potential to compensate for the performance decrease in many ways such as increasing annual generation and reducing initial cost. This paper contributes by providing some insights into the economic performance and market of residential PV installations in China.